Perlindungan Hukum Bagi Konsumen Terhadap Skincare Bermerkuri Berdasarkan Hukum Positif Di Indonesia - Hikmawan, Regina Anynditha Putri Hikmawan; Budi Sutrisno (Bagian Hukum Bisnis Fakultas Hukum Universitas Mataram, 2024)
THE LEGAL PROTECTION FOR CUSTOMERS FROM SKINCARE CONTAINING MERCURY ACCORDING TO INDONESIA POSITIVE LAW ABSTRACT This study describes the legal protection for consumers from skincare containing mercury according to Indonesian Positive Law, as well as identifies the responsibility of distributors of such products. It also reviews the measures taken by Indonesian FDA Branch Mataram in supervising such products’ distribution. This is a normative-empirical study, with statute, conceptual, juridical, and sociological approaches. Results of this study show that the legal protection for customers from skincare-containing-mercury are provided in preventive and corrective measures. The responsibility of such products’ distribution could be imposed administrative, criminal, as well as civil sanctions. In addition, Indonesian FDA Branch Mataram supervises skincare distribution by conducting Pre-Market and Post-Market supervision.